2019
DOI: 10.1039/c9nr04010b
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional perovskite nanoplatelet synthesis using in situ photophysical monitoring to establish controlled growth

Abstract: CsPbBr3 nanoplatelets are synthesized with fine control over size, thickness and optical properties. In situ photoluminescence measurements are used to optimize platelet growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In this study, in the Pb–halide routes, Δ E = 140–150 meV, which indicates a significantly larger change from nuclei size to grain size. Although the chemistry used for the synthesis of 3D MAPbI 3 films is different than that for the synthesis of nanocrystals (typically no surface ligands are used for the synthesis of thin films), we propose that nucleation starts on the nanometer scale (or sub‐micrometer scale), similar to the initial stages of nanocrystal growth . In the latter, ligands would terminate the growth of nanocrystals and therefore dominate spectral PL emission (size effect), while in thin films, PL emission is related to the bandgap.…”
Section: Resultsmentioning
confidence: 96%
“…In this study, in the Pb–halide routes, Δ E = 140–150 meV, which indicates a significantly larger change from nuclei size to grain size. Although the chemistry used for the synthesis of 3D MAPbI 3 films is different than that for the synthesis of nanocrystals (typically no surface ligands are used for the synthesis of thin films), we propose that nucleation starts on the nanometer scale (or sub‐micrometer scale), similar to the initial stages of nanocrystal growth . In the latter, ligands would terminate the growth of nanocrystals and therefore dominate spectral PL emission (size effect), while in thin films, PL emission is related to the bandgap.…”
Section: Resultsmentioning
confidence: 96%
“…Reproduced with permission. [39] Copyright 2019, Royal Society of Chemistry. e) Evolution of PL peak position and corresponding FWHM during nanocrystal growth.…”
Section: Monitoring Of Synthesismentioning
confidence: 99%
“…by hot injection or halide precursor injection) red shifting of the PL maximum and peak narrowing is observed until PL emission wavelength is constant indicating nucleation and growth until growth is terminated (Figure 3d). [39] [90] It was concluded that the size of the nanocrystals cannot be controlled by the growth time but is controllable with the reaction temperature. [39] [89] In these studies nucleation kinetics were not quantified, nor attempted to interpret via classical nucleation theory but the results demonstrate that in situ PL could be used to extract detailed kinetics with respect to synthesis condition such as temperature or chemical composition.…”
Section: Monitoring Of Synthesismentioning
confidence: 99%
See 2 more Smart Citations